2006
DOI: 10.1021/op068010t
|View full text |Cite
|
Sign up to set email alerts
|

On the Synthesis of 1,1-Diamino-2,2-dinitroethene (FOX-7) by Nitration of 4,6-Dihydroxy-2-methylpyrimidine

Abstract: The synthesis of 1,1-diamino-2,2-dinitroethene (FOX-7) by nitration of 4,6-dihydroxy-2-methylpyrimidine and hydrolysis of the resulting intermediate 2-dinitromethylene-5,5-dinitropyrimidine-4,6-dione has been studied. By varying the reaction parameters the optimal conditions for the synthesis of FOX-7 have been identified and gave a >90% yield of the pure product. The optimised process allowed the spent acid to be recycled without loss of yield, with almost stoichiometric consumption of nitric acid. The purity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 4 publications
2
35
0
Order By: Relevance
“…5,6 Such facts indicated that the activity free energy of the nitration should be considerably low, and the HSO 4 À -induced path A may be more favorable way than the direct path, which is in very good agreement with the experimental results. 6 Additionally, in view of the fact that a higher H 2 SO 4 concentration may benet an easier formation of NO 2 + along with a more difficult dissociation of H 2 SO 4 to form HSO 4 À , the concentration of H 2 SO 4 should be well controlled.…”
Section: Resultssupporting
confidence: 82%
“…5,6 Such facts indicated that the activity free energy of the nitration should be considerably low, and the HSO 4 À -induced path A may be more favorable way than the direct path, which is in very good agreement with the experimental results. 6 Additionally, in view of the fact that a higher H 2 SO 4 concentration may benet an easier formation of NO 2 + along with a more difficult dissociation of H 2 SO 4 to form HSO 4 À , the concentration of H 2 SO 4 should be well controlled.…”
Section: Resultssupporting
confidence: 82%
“…Micro-sized FOX-7, which was synthesized by nitration of 4,6-dihydroxy-2-methylpyrimidine and subsequent hydrolysis of the resulting intermediate 2-dinitromethylene-5,5-dinitropyrimidine-4,6-dione [7], was recrystallized one time in 1-methyl-2-pyrrolidinone (NMP)/H 2 O (70/30) and the purity was higher than 99.7%. Ultra-pure water (resistivity = 18.2 M cm) was produced using a Milli-Q apparatus (Millipore) and filtered using an inorganic membrane with a pore size of 0.02 m (Whatman International, Ltd.) just before use.…”
Section: Chemicalsmentioning
confidence: 99%
“…Up to now, most of the researches have focused on the theoretical calculation, structural properties, improvement of synthesis routes, and study of thermolysis and sensitivity of FOX-7 microparticles [2][3][4][5][6][7][8][9][10][11], while few studies on FOX-7 nanostructures. However, similar to other inorganic nanostructures and organic nanostructures, energetic materials also exhibit some size-dependent properties, such as sensitivity, thermal stability, operational performance, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…18 Table 5. We can see the calculated results are all less than the experimental results and the deviations of the two results are very small, which are consistent well with the results of specific heat capacity.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%